The Promise - Kosminsky, Peter; Higgs, David; Foy, Claire; Cooke, Christian; Tiran, Itay (Channel 4, 2011)
Claire Foy and Christian Cooke lead an international cast, including Itay Tiran, Haaz Sleiman, Ali Sulaiman and Perdita Weeks, in Peter Kosminsky's new four-part drama serial. Just as 18-year-old Londoner Erin sets off to spend summer in Israel with her best friend, Eliza, she unearths an old diary belonging to her seriously ill grandfather, Len. Intrigued by the life of this old man she barely knows, she takes the diary with her, and is stunned to learn of his part in the post-WWII British peace-keeping force in what was then Palestine. Left to her own devices when Eliza begins National Service in the Israeli army, Erin witnesses the complexities of life - for both Jews and Arabs - in this troubled land. And as Len's story comes to life from the pages of the diary, Erin discovers the disturbing truths about his time in Palestine and the atrocities he witnessed in the 1940s. Retracing Len's steps in modern-day Israel, Erin sets out on a heart-breaking journey in an effort to understand and fulfil a promise made by her grandfather over 60 years ago. [www.amazon.co.uk]
Keywords: DVD-Video